Systematic Literature Review (SLR) on Annuity Modeling of Plantation Replanting Cost Reserves Based on the Cobb-Douglas Model - Fasa, Rayyan Al Muddatstsir; Napitupulu, Herlina; Sukono, Sukono (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Annuity is a financial concept that involves a series of periodic payments or receipts. In oil palm plantation management, the annuity concept is adapted to model and estimate the reserves required for replanting costs over time. The Cobb-Douglas model is a model that considers the contribution of various factors in the production process. This model can be used to estimate the income of plantations. This study discusses the Systematic Literature Review on Annuity Modeling of Plantation Replanting Cost Reserves through the application of the Cobb-Douglas Model using the Reporting Method of Choice for Systematic Review and Meta-Analysis (PRISMA) method. The study systematically collected and analyzed relevant literature from Scopus, Science Direct, Dimensions, and SAGE databases. The review followed a structured methodology that included four main stages: Identification, Screening, Eligibility, and Inclusion. Analysis was conducted on the datasets obtained at the Eligibility and Inclusion stages. Statistical techniques facilitated by the